THE INFLUENCE OF PROMOTION, PRICE PERCEPTION, LOCATION AND SERVICE QUALITY ON CUSTOMER SATISFACTION AT SADIMO BARBERSHOP JEMBER - Maulana Yusuf, Muhammad Beny; Sumowo, Seno; Rusdiyanto, Rusdiyanto (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
The service industry is currently a very large and rapidly growing creative economy sector business and is very much needed in consumer activitiesBarbershop is one of the businesses that is currently growing. One of the 17 subsectors that make up Indonesia's creative economy is barbershop. The Ministry of Tourism and Creative Economy (Kemenparekraf) states that the sector that makes the largest contribution to GDP is the creative economy. This study was conducted to determine the effect of promotional quality, perceived price, location and service quality on customer satisfaction at Sadimo Barbershop Jember. Multiple linear regression analysis was used in this study. The population used is from all walks of life, with the criteria for respondents being consumers who have used the services of Sadimo Barbershop Jember at least twice. Purposive sampling technique was applied using a sample of 95 people. Partial test results (t test) showed a significant effect of promotion variables on customer satisfaction, a significant effect of price perception variables on customer satisfaction, a significant effect of location variables on customer satisfaction, and no significant effect of service quality variables on customer satisfaction.